High Resolution Study of 13C2H4 in the Region of 1700 - 2150 cm-1 : The v8 + v10, v7 + v8, v4 + v8, v6 + v10, and v3 + v10 Bands - Gromova O. V. Olga Vasilievna; Morzhikova Yu. B. Yuliya Borisovna; Onopenko G. A. Galina A.; Bekhtereva E. S. Elena Sergeevna; Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Bauerecker Z. (S.) H. Zigurd (Sigurd) Hermann (Poster session J, 2016)
Title screen